Individual Abilities of Managers sebagai Mediasi Pengaruh Self-Leadership terhadap Entrepreneurial Intention pada Generasi Millenial Kota Malang - Choirul Anam; Sudarmiatin Sudarmiatin; Agus Hermawan (Universitas Diponegoro, 2023)
This paper explains Individual Abilities of Managers as a mediation of the influence of Self-Leadership on Entrepreneurial Intention in the Millennial Generation of Malang City. Types of quantitative research with explanatory research methods. The sample taken was millennials as many as 161 respondents. data collection with questionnaires and using Smart-PLS as its analysis tool. The results showed that Self Leadership directly has a significant effect on Entrepreneurial Intention. Furthermore, Self Leadership has a significant effect on Individual Abilities of Managers has a significant effect on Entrepreneurial Intention. Then, Individual Abilities of Managers have a significant effect on Entrepreneurial Intention. Finally, Individual Abilities of Managers are indirectly capable of being partial mediating variables.Artikel ini menjelaskan Individual Abilities of Managers sebagai mediasi pengaruh Self-Leadership terhadap Entrepreneurial Intention pada generasi Millenial Kota Malang. Jenis penelitian kuantitatif dengan metode explanatory research. Sampel yang diambil adalah generasi millenial sebanyak 161 responden. Pengumpulan data dengan kuesioner dan menggunakan Smart-PLS sebagai alat analisisnya. Hasil penelitian menunjukkan bahwa secara langsung Self Leadership berpengaruh signifikan terhadap Entrepreneurial Intention. Selanjutnya, Self Leadership berpengaruh signifikan terhadap Individual Abilities of Managers berpengaruh signifikan terhadap Entrepreneurial Intention. Kemudian, Individual Abilities of Managers berpengaruh signifikan terhadap Entrepreneurial Intention. Terakhir, Individual Abilities of Managers secara tidak langsung mampu menjadi variabel mediasi bersifat mediasi sebagian.